Pharmacologic Management of Aggression in Adults with Intellectual Disability - Roy, Durga; Hoffman, Pamela; Dudas, Melissa; Mendelowitz, Alan (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Introduction: Aggression is a common behavioral problem seen in patients with intellectual disabilities (ID). The safety and efficacy of second generation antipsychotics (SGAs), mood stabilizers and antidepressants in the management of aggression in these individuals have minimally been studied. This review aims to 1) summarize the studies conducted using second generation antipsychotics, mood stabilizers and antidepressants in treating aggressive behaviors in patient with ID and 2) determine based on the existing literature, which medications have been examined in the most rigorous study design that might suggest the most efficacy for use in clinical practice. Methods: Literature searches using PUBMED Central, CINAHL Plus, PsychINFO, and Embase databases were conducted using the following terms: intellectual disability/disabilities, mental retardation, developmental disability/disabilities, aggression, agitation, behavior disorder, adult, treatment, management. Studies predominantly including children with ID, and autism/pervasive developmental disabilities spectrum disorders were excluded. Analyses were done by class of medication: SGAs, mood stabilizers and antidepressants. The primary outcome measure was reduction in aggressive or self injurious behaviors as measured by each individual study. Results: The most rigorous study designs found using these agents were randomized controlled trials (RCT). A total of 10 RCTs were found, the majority being with risperidone (3) and lithium (2). Treatment with risperidone showed reduction in aggression when compared to placebo in most RCTs with the exception of one study in which risperidone was not better than placebo. Both lithium studies showed reduction in aggression when compared to placebo. The most abundant literature exists in retrospective chart reviews. The most commonly studied agent was risperidone which showed reduction in aggression in majority of the studies. Conclusions: Limited data exists for treatment of aggression in adults with ID. There are very few studies examining pharmacologic agents using RCTs. Given that risperidone and lithium were the most commonly studied agents in the most rigorous experimental design, it is suggested that these two agents prove efficacious for treatment of aggression in patients with ID. Limitations to most of these studies included concomitant psychotropic administration with variations in types and dosing, severity of ID, and the idea that a wide variety of aggression scales were used to assess outcome. Further research with more scientific rigor is required in this field.